2018
DOI: 10.1016/j.neurobiolaging.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of resting-state functional cortical connectivity in patients with dementia due to Alzheimer's and Lewy body diseases: an EEG study

Abstract: Previous evidence showed abnormal posterior sources of resting-state delta (<4 Hz) and alpha (8-12 Hz) rhythms in patients with Alzheimer's disease with dementia (ADD), Parkinson's disease with dementia (PDD), and Lewy body dementia (DLB), as cortical neural synchronization markers in quiet wakefulness. Here, we tested the hypothesis of additional abnormalities in functional cortical connectivity computed in those sources, in ADD, considered as a "disconnection cortical syndrome", in comparison with PDD and DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 164 publications
7
71
0
Order By: Relevance
“…Here the authors associated the reduced hubness with a more severe cognitive impairment in DLB (van Dellen et al, ). In a more recent study, Babiloni and colleagues reported reduced interhemispheric connectivity patterns in dementia patients (Babiloni et al, ), with weaker connections in AD compared with DLB over posterior and temporal regions within the α range; this intra‐hemispheric connection showed no differences between DLB and PDD. According to the authors, this aspect is associated with the fact that the pathology is similar in both LBDs, that is, DLB and PDD.…”
Section: Introductionmentioning
confidence: 97%
“…Here the authors associated the reduced hubness with a more severe cognitive impairment in DLB (van Dellen et al, ). In a more recent study, Babiloni and colleagues reported reduced interhemispheric connectivity patterns in dementia patients (Babiloni et al, ), with weaker connections in AD compared with DLB over posterior and temporal regions within the α range; this intra‐hemispheric connection showed no differences between DLB and PDD. According to the authors, this aspect is associated with the fact that the pathology is similar in both LBDs, that is, DLB and PDD.…”
Section: Introductionmentioning
confidence: 97%
“…LLC characteristics of EEG connectivity are not affected by the instantaneous propagation of neural ionic currents that are partly due to head volume conduction effects. The LLC of posterior alpha sources was found to be decreased in patients with aMCI compared to normal controls (Babiloni et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
“…The hippocampus is an important node of the DMN that modulates EEG alpha activity. The DMN regions, and the hippocampus in particular, are preferentially vulnerable to degenerative processes that are accompanied by progressive decreases in LLC of alpha sources (Babiloni et al, 2018). In MCI and prodromal AD, alpha disconnection in brain networks is related to progressive cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations